DETERMINATION OF UROPEPSIN IN URINE IN IRON DEFICIENCY ANAEMIA IN EARLY CHILDREN AND ITS SIGNIFICANCE - Kholmuradova Zilola Ergashevna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation.  WHO  data  according  to,  every  1.5  billion  per  year  more  than anemia with patients to list is taken, almost 50% of cases iron shortage with related to UNICEF's Micronutrient Initiative iron shortage anemia to work of competence serious decline,  mothers  of  death  increase,  child  physical  and  mental  to  develop  negative impact to show such as economic importance has was factors between dependency shows . This and iron shortage anemia diagnosis early in the making various kind diagnostic methods question In children blood in diseases urine in the composition uropipsin amount determination less learned because of , we iron shortage anemia there is in children him/her to determine current that We knew . The work purpose so , anemia weight to the level related in the case in urine uropepsin Definition . Materials and methods . From 1 to 3 years old was every kind severe iron deficiency anemia 42 children were examined . Stomach fermentative function in urine issued uropepsin amount with Pepsinogen stomach mucus on the floor working will be issued and to the blood  decreased  by  1%  urine  with  uropepsin  in  appearance  Research  for  morning issued from urine last second part taken, its amount and first and second pee between past time record The patient was in children in urine uropepsin amount anemia weight level into account received without Iron deficiency was detected . in anemia in urine uropepsin  amount  decrease  was  shown.  Even  light  level  uropepsin  also  in  anemia amount in urine healthy was to children than much lower (P